Rancang Bangun Aplikasi Web Manajemen Penjualan dan Produksi Lilin Pada PO De Santo Lilin Lembata Terang - Tedy, Frengky; Asan, Maria Stefany De Santo Ina Barek (JATISI, 2025)
PO. De Santo Lilin Lembata Terang is a sole proprietorship (PO) that focuses on the production and sale of candles located in Lamahora, Lembata Regency, East Nusa Tenggara. So far, the production and sales system is still done manually, namely by using Microsoft Excel and handwriting. Where, the use of this method often causes problems, such as loss of recorded data, inconsistencies between recorded sales data and production data which causes differences between the amount of production results and consumer needs. This not only hinders operational efficiency, but also has an impact on consumer satisfaction and the company's potential income. For this reason, the purpose of this study is to design and build an application that can be used as a solution to overcome these problems. The method used in developing this application is the Waterfall method. The results of this study are a web application for candle sales and production management at PO. De Santo Lilin Lembata Terang which can record candle production results, sales results, employee data, candle product data and raw material data. This application can also generate sales reports, production reports, raw material usage reports and employee performance reports which will be used as a basis for payroll.